2016
DOI: 10.1016/j.bbrc.2016.06.113
|View full text |Cite
|
Sign up to set email alerts
|

In vivo inhibition of tumor progression by 5 hydroxy-1,4-naphthoquinone (juglone) and 2-(4-hydroxyanilino)-1,4-naphthoquinone (Q7) in combination with ascorbate

Abstract: The purpose of the study was to obtain further in vivo data of antitumor effects and mechanisms triggered by juglone and Q7 in combination with ascorbate. The study was done using Ehrlich ascites tumor-bearing mice. Treatments were intraperitoneal every 24 h for 9 days. Control group was treated with excipient. Previous tests selected the doses of juglone and Q7 plus ascorbate (1 and 100 mg/kg, respectively). Samples of ascitic fluid were collected to evaluate carbonyl proteins, GSH and activity of antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…Notably, enhanced glycolysis or FAO inhibition prevents murine iTreg differentiation 10, 27, 47 . The inhibition of glycolysis, for example by using 2-Deoxy-D-Glucose (2-DG), promotes iTreg polarization by regulating mTOR activity 47 , which could be linked to its downregulation of HIF-1α expression, as described in tumor cell lines 48, 49 . As previous studies described HIF-1α as an important regulator of cell metabolism 10, 18, 50 , we thus analyzed the effect of IL-1β and DMOG on Treg metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, enhanced glycolysis or FAO inhibition prevents murine iTreg differentiation 10, 27, 47 . The inhibition of glycolysis, for example by using 2-Deoxy-D-Glucose (2-DG), promotes iTreg polarization by regulating mTOR activity 47 , which could be linked to its downregulation of HIF-1α expression, as described in tumor cell lines 48, 49 . As previous studies described HIF-1α as an important regulator of cell metabolism 10, 18, 50 , we thus analyzed the effect of IL-1β and DMOG on Treg metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Free radicals can attack DNA at C4 of deoxyribose generating products as propenal, which react with 2-thiobarbituric acid and produce the TBARS formation [ 40 ]. In both T24 and MCF-7 cells, we found that Q7 provoked elevated levels of intracellular ROS [ 23 , 25 , 35 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…This inhibition induced cancer cells senescence [ 10 ], reduction of DNA damage, and inhibition of in vivo tumor growth [ 11 ]. It also leads to an inhibition of in vivo tumor progression by triggering apoptosis, cell cycle arrest, suppression of HIF-1, and uncoupling glycolytic metabolism [ 25 ]. All these effects have been attributed to its ability to generate ROS through quinone redox-cycling.…”
Section: Introductionmentioning
confidence: 99%
“…Juglone demonstrated antitumour efficacy in in vivo models of prostate, intestinal, and Ehrlich ascites carcinoma [ 106 , 115 , 179 , 180 , 181 ]. Juglone 200 ppm was fed to weanling F344 male rats concurrently with the induced initiation phase of carcinogenesis.…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Ascorbate potentiated juglone-mediated cell-cycle arrest and apoptosis, increasing the number of cells in G1 and the expression of cell-cycle inhibitors like p53 and p16. Furthermore, only in the presence of ascorbate, juglone was able to reduce the expression of cyclin A. Apoptosis-wise, the presence of ascorbate made possible to detect cleaved PARP, and increased the Bax/Bcl2 ratio [ 181 ].…”
Section: Anticancer Activitymentioning
confidence: 99%